تقييم معلومات مرافقي مصابي الحرب ذوي الإعاقة الحركية حول منع حدوث و تطور القرح الانضغاطية - زمزم, سوزان (Latakia University Journal -Medical Sciences Series, 2019)
Pressure sore still exists as a common health problem and occurs in both hospitals and houses, affecting all age groups, but mostly occurring among the patients with limited mobility. Moreover, it bears a growing financial burden, increases the length of stay in the hospital, affects quality of life, and increases morbidity and mortality. This study aimed to assessing the companions’ knowledge of immobilized war casualties’ about prevent the occurrence and development of pressure sore. The researcher used descriptive method, the questionnaire was used to collect the study data from 52 companions of immobilized war casualties, who were chosen by purposive sample from zahy Al-Azrak and Al-Assad hospitals and from charities that look after war-wounded in Lattakia city. The findings indicated that a high percentage of the companions (82.7%) had low level of knowledge on prevent the occurrence and development of pressure sore, only (17.3%) of them had a medium level while nobody of them had a high level of knowledge. Finally, this study recommended applying educational program and regular training courses can be useful in updating the knowledge of participants about pressure sore prevention. ما زالت القرح الانضغاطية مشكلة صحية شائعة تحدث في كل من المشافي و المنازل، تصيب كل الفئات العمرية، لكن تكون أكثر شيوعا بين مرضى الإعاقة الحركية. علاوة على ذلك، تسبب القرح الانضغاطية عبئاً ماديا متزايداً، تزيد من فترة بقاء المريض في المشفى، تؤثر على نوعية الحياة، و تزيد من نسبة الإمراضية و الوفاة. هدفت هذه الدراسة إلى تقييم معلومات مرافقي مصابي الحرب ذوي الإعاقة الحركية حول منع حدوث وتطور القرح الانضغاطية. استخدم الباحث المنهج الوصفي، وقد استخدمت الاستبانة على عينة تكونت من 52 مرافق من مرافقي مصابي الحرب العسكريين ذوي الإعاقة الحركية تم اختيارهم بالطريقة القصدية من سجلات المرضى بمشفى زاهي الأزرق و مشفى الأسد والجمعيات الخيرية التي تعنى بجرحى الحرب في مدينة اللاذقية. أشارت النتائج إلى أن النسبة الأعلى من المرافقين )82.7%( مستوى معلوماتهم ضعيف, و (17.3%) مستوى معلوماتهم متوسط, بينما لا أحد منهم مستوى معلوماته عالي. أخيرا أوصت هذه الدراسة بضرورة اشراك مرافقي مصابي الحرب ذوي الإعاقة الحركية ببرامج تثقيفية و دورات تدريبية مستمرة حول الوقاية من القرح الانضغاطية الذي من شأنه أن يطور و يحسن معلوماتهم في هذا المجال.